Zapomniana rezydencja w Strawczynie koło Kielc - Kajzer, Leszek (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
The paper includes a description of finds recovered in the village Strawczyn, near Kielce. Conservatory and archaeological works conducted there in 1990 resulted in uncovering of hardly preserved relics of a masonry building raised from local lime stone. Portable relics found in cultural layers inside the building and nearby allowed to date the object to about 1600 till the mid 17th century. Poorly preserved relics of foundation walls enabled to reconstruct the projection of the building and its interior division. It was a two tract and in the utmost axles three tract house built on a plan of an elongated rectangular (19 by 33 m) clung in the corners by octahedral towers. In the northern tract, on both sides of a big room situated axially there were two smaller rooms, whereas in the southern tract there were five bigger and two small rooms. The body of the building (on the ground floor) consisted of twelve rooms on a square plan, while in the towers there were four rooms on a round plan (ca. 4 m in diameter). The building (remnant of a manor house or a palace) had two floors and was covered with roof tiles. Its southern elevation was enriched by an elongated projection which could have been a remnant of a shallow loggia or of some sort of arcade construction stuck to the body of the building. The residence in Strawczyn was connected with investment activity of Jakub Stanisław Gawroński, Wieluń castellan in the years 1608-1624. The ground plan, the design of the described building, as well as its scale show evident similarity to an early baroque palace in Kielce, raised by Cracow bishop Jakub Zadzik (1637-1641), and consequently with a slightly bigger Tarło palace in Podzamcze Piekoszowskie, near Kielce, which was an imitation of the Kielce residence. High architectural rank of both palaces may suggest that the palace in Strawczyn may be considered as their imitation. However, the fact that the palace in Strawczyn dates to the first quarter of the 17th century excludes such a possibility. In the final part of the text the author presents his own, possibly controversial interpretation. He suggests that the palace in Strawczyn is not an imitation of the palaces in Kielce and Podzamcze Piekoszowskie, but genetically it expresses the changes which residential buildings obviously underwent in the horizon of the year 1600. At that time, typical for the 16th century, compact in plans, masonry manor houses began to take a form of massive blocks built on elongated rectangular plans, clung in the corners by cylindrical hexahedral or octahedral towers. These changes were obviously influenced by trends in European early baroque palaces although we can not talk about a direct influence of "Italianism" of contemporary architecture. The latter formed, axially founded, symmetrical blocks of the residences of the magnates from the epoch of early baroque, which were raised in the second quarter of the 17th century, namely the palaces in Kielce and Podzamcze Piekoszowskie.